COLLABORATIVE GOVERNANCE DALAM PEMBANGUNAN INFRASTRUKTUR JALAN ANTAR DESA MUARA LEMATANG – RANTAU TAHUN 2022 - Permatasari, Lidya; Kariem, M.Qur’anul; Nofrima, Sanny (Governance, 2025)
Rantau Bayur Village faces problems in regional development due to poor connecting road facilities bordering Muara Lematang Village. The PUPR Office of Muara Enim Regency has given authority to Muara Lematang Village to cooperate with Rantau Bayur Village in road construction. This study aims to determine the stages of collaborative governance drivers in road infrastructure development between Muara Lematang Village - Rantau Bayur. This study uses a qualitative method with a Phenomenological approach. Based on the results of the study, collaborative governance in road infrastructure development there is a village boundary conflict between Muara Lematang Village and Rantau Bayur Village. Village road construction is carried out through deliberations involving Village Apparatus, BPD, Non-Governmental Organizations, Private Parties and the Community to be directly involved in the preparation of planning, implementation, budgeting, and maintenance of road construction. The construction of this village road is funded from the district APBD. The resolution of the boundary determination problem that has been traced by Topdam II Sriwijaya and has been agreed upon with the issuance of Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 95 of 2022 concerning the Territorial Boundaries of Banyuasin Regency and Muara Enim Regency, South Sumatra Province. Signed directly by both village parties.